2019
DOI: 10.4236/ce.2019.1013260
|View full text |Cite
|
Sign up to set email alerts
|

Challenges Faced by Students and Teachers on Writing Skills in ESL Contexts: A Literature Review

Abstract: English is an international language and in demand today. English is by far the most widely used language around the world. However, English language writing has always been a challenge for second language students to master. Developing students' ability in writing is one of the major challenges faced by the ESL teachers in most schools nowadays. Nevertheless, writing has always been a major difficulty faced by students in English language learning, especially in elementary schools. Not only that, teachers are… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
98
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(109 citation statements)
references
References 6 publications
5
98
1
5
Order By: Relevance
“…The study explored various and common challenges/difficulties during writing the research proposals and projects such as: difficulty in deciding the topic for research, lack of good knowledge of the methodology, the inability of finding modern, specialized and related references, lack of interest in research, lack of understanding of the subject matter, lack of time, and research guiding. A similar study was done by Moses and Mohamad (2019) and found that writers faced challenges such as lack of vocabulary, grammar, and spelling skills. They are sometimes not ready for the writing activities besides not having enough exposure to reading materials.…”
Section: Difficulties Writers Facementioning
confidence: 62%
“…The study explored various and common challenges/difficulties during writing the research proposals and projects such as: difficulty in deciding the topic for research, lack of good knowledge of the methodology, the inability of finding modern, specialized and related references, lack of interest in research, lack of understanding of the subject matter, lack of time, and research guiding. A similar study was done by Moses and Mohamad (2019) and found that writers faced challenges such as lack of vocabulary, grammar, and spelling skills. They are sometimes not ready for the writing activities besides not having enough exposure to reading materials.…”
Section: Difficulties Writers Facementioning
confidence: 62%
“…Motivating the students continues to be a major hurdle in teaching writing. Beyond being disobedient, disinterest among the L2 learners is obvious (Mukminin, 2014;Moses et al, 2019). Reluctance in learning reflects the lack of motivation among the learners (Abrar, 2016).…”
Section: The Problems Of Teaching Writingmentioning
confidence: 99%
“…In González Fernández and Schmitt (2017) vocabulary has been described as crucial components that influence the productive and receptive skills in a language. This means that vocabulary learning influences the reading, writing, listening and speaking skills which determine the level of proficiency in any language (Moses & Mohamad, 2019). In that sense, the vocabulary has been defined as key in helping learners achieve better reading in a new language.…”
Section: Vocabularymentioning
confidence: 99%